Brain flexibility associated with need for cognition contributes to creative achievement. (27th August 2019) - He, Li; Zhuang, Kaixiang; Li, Yu; Sun, Jiangzhou; Meng, Jie; Zhu, Wenfeng; Mao, Yu; Chen, Qunlin; Chen, Xiaoyi; Qiu, Jiang
Abstract: Advances in graph‐theoretic models of networks have made it possible to investigate the topological properties of the human brain across time and space. Brain flexibility is defined as the frequency with which brain regions switch between different functional modules over time and has been shown to correlate with higher‐order cognitive functions. Need for cognition (NFC) refers to a personality trait to engage in and enjoy effortful cognitive endeavors and usually has a positive effect on diverse cognitive activities (e.g., creativity), which may also be closely related to brain flexibility. Here, we tested whether the flexibility of a large‐scale brain network associated with NFC facilitated creative achievement. Robust correlation analyses showed that NFC correlates with the flexibility of the insula, the medial prefrontal cortex, and the putamen at the node level. Several large‐scale brain networks whose flexibility also correlated with NFC, including the default mode network, salience network, subcortical network, ventral attention network, and control network, imply that higher NFC individuals may exhibit better cognitive abilities, such as executive control, salient detection, spontaneous thought, and motivation function. Interestingly, only global flexibility acted as a mediator in the relationship between NFC and creative achievement, suggesting that the mediating mechanism may involve an interaction between distinct regions or large‐scale networks across the entire brain instead of the functional characteristic of local regions. Together, we demonstrate that the higher NFC is, the more flexible the brain, which may provide a potential insight into the acquisition of creative achievement. Abstract : By applying the multilayer network method and quantifying the frequency of each node transition between different functional modules, we demonstrated that the higher the need for cognition (NFC) is, the more flexible the brain. We also found that global flexibility rather than a specific network acts as a mediator in the correlation between NFC and creative achievement. Hence, we suggest that the tendency to engage in and enjoy effortful cognitive endeavors may alter brain network dynamics at resting state, which contributes to the acquisition of creative achievement.